2022
DOI: 10.3390/cimb44080235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Inclusion of β-Hydroxy-β-Methylbutyrate on Growth Performance, Fat Deposition, Bile Acid Metabolism, and Gut Microbiota Function in High-Fat and High-Cholesterol Diet-Challenged Layer Chickens

Abstract: Excessive lipid deposition in layer chickens due to inappropriate feeding adversely affects egg production; however, nutritional manipulation methods to deal with this issue are still limited. β-hydroxy-β-methylbutyrate (HMB), a metabolite of L-leucine, was recently reported as a lipid-lowering nutrient in mice and pigs, although its role in layers had not been investigated. Here, we employed high-fat and high-cholesterol diet (HFHCD)−challenged growing layers as an obese model to explore HMB function in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
(61 reference statements)
2
12
0
Order By: Relevance
“…This result confirmed that the reduced broiler performance was also related to the lower serum IGF‐1 level 8 . These observations support the idea that the low‐protein diet supplemented with HMB positively affects overall performance 19,20,34,36 . In the present study, the diet with HMB had similar muscle yields and meat quality to those from broilers fed with SPD by increasing the development of early gut and small intestine morphology.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This result confirmed that the reduced broiler performance was also related to the lower serum IGF‐1 level 8 . These observations support the idea that the low‐protein diet supplemented with HMB positively affects overall performance 19,20,34,36 . In the present study, the diet with HMB had similar muscle yields and meat quality to those from broilers fed with SPD by increasing the development of early gut and small intestine morphology.…”
Section: Discussionsupporting
confidence: 89%
“…8 These observations support the idea that the low-protein diet supplemented with HMB positively affects overall performance. 19,20,34,36 In the present study, the diet with HMB had similar muscle yields and meat quality to those from broilers fed with SPD by increasing the development of early gut and small intestine morphology. This result did not confirm that the breast muscle is more sensitive to HMB than the leg muscle with different fiber types.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Inappropriate feeding in layer chickens results in excessive fat deposition and metabolic disorders, thereby affecting egg production. Considering the poultry industry, Liao et al found that dietary supplementation with β-hydroxy-β-methylbutyrate could reduce abdominal lipid deposition in layer chickens through enhancing hepatic bile acid synthesis and gut microbiota function [8].…”
mentioning
confidence: 99%